2008
DOI: 10.1002/jat.1406
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant responses and metal accumulation in tissues of Nile tilapia Oreochromis niloticus under Zn, Cd and Zn + Cd exposures

Abstract: We investigated the effects of Zn, Cd and a Zn + Cd mixture on antioxidant parameters and metal accumulation in Oreochromis niloticus. Fish were exposed to 0.5 and 5.0 mg l(-1) Zn, 0.1 and 1.0 mg l(-1) Cd, and 0.5 mg l(-1) Zn + 0.1 mg l(-1) Cd and 5.0 mg l(-1) Zn + 1.0 mg l(-1) Cd mixtures for 7 and 28 days to determine Zn and Cd accumulation, reduced glutathione (GSH) level and glucose-6-phosphate dehydrogenase (G6PD) activity in gill and liver. There was increasing accumulation of the metals in the tissues w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(23 citation statements)
references
References 52 publications
2
16
0
2
Order By: Relevance
“…1). The results of this study are in agreement with our previous study (Fırat et al 2009) which reported an elevation of GSH levels in the gill and liver of Oreochromis niloticus in response to single and combined Zn and Cd exposure for 7 and 28 days, especially at the higher concentrations. GSH is considered a first line of cellular defence against metals by chelating and detoxifying them, scavenging oxyradicals and participating in detoxification reactions catalyzed by glutathione peroxidases (Sies 1999).…”
Section: Gsh Levelsupporting
confidence: 95%
“…1). The results of this study are in agreement with our previous study (Fırat et al 2009) which reported an elevation of GSH levels in the gill and liver of Oreochromis niloticus in response to single and combined Zn and Cd exposure for 7 and 28 days, especially at the higher concentrations. GSH is considered a first line of cellular defence against metals by chelating and detoxifying them, scavenging oxyradicals and participating in detoxification reactions catalyzed by glutathione peroxidases (Sies 1999).…”
Section: Gsh Levelsupporting
confidence: 95%
“…Accumulation of Cd 2? in fish could stimulate the production of ROS, which then reacts with susceptible biological macromolecules, resulting in changes to LPO and antioxidant defenses (Firat et al 2009). In the present study, ROS levels of gills did not significantly change over various exposure times, but were elevated Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that heavy metals induce ROS in fish, and others have examined antioxidant gene expressions to decrease oxidative damage (Firat et al 2009;Cao et al 2010). Such defense mechanisms have been proposed as Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Normal homoeotasis status requires a balance between prooxidant and antioxidant systems. Exceeding the defensive capability of antioxidant systems can induce adverse eff ects (van der Schalie et al, 2004;Firat et al, 2009).…”
Section: Introductionmentioning
confidence: 99%